An Open‐Structured Matrix as Oxygen Cathode with High Catalytic Activity and Large Li2O2 Accommodations for Lithium–Oxygen Batteries. Issue 18 (24th March 2018) - Lin, Xiaodong; Yuan, Ruming; Cai, Senrong; Jiang, Youhong; Lei, Jie; Liu, San‐Gui; Wu, Qi‐Hui; Liao, Hong‐Gang; Zheng, Mingsen; Dong, Quanfeng
Abstract: The nonaqueous lithium–oxygen (Li–O2 ) battery is considered as one of the most promising candidates for next‐generation energy storage systems because of its very high theoretical energy density. However, its development is severely hindered by large overpotential and limited capacity, far less than theory, caused by sluggish oxygen redox kinetics, pore clogging by solid Li2 O2 deposition, inferior Li2 O2 /cathode contact interface, and difficult oxygen transport. Herein, an open‐structured Co9 S8 matrix with sisal morphology is reported for the first time as an oxygen cathode for Li–O2 batteries, in which the catalyzing for oxygen redox, good Li2 O2 /cathode contact interface, favorable oxygen evolution, and a promising Li2 O2 storage matrix are successfully achieved simultaneously, leading to a significant improvement in the electrochemical performance of Li–O2 batteries. The intrinsic oxygen‐affinity revealed by density functional theory calculations and superior bifunctional catalytic properties of Co9 S8 electrode are found to play an important role in the remarkable enhancement in specific capacity and round‐trip efficiency for Li–O2 batteries. As expected, the Co9 S8 electrode can deliver a high discharge capacity of ≈6875 mA h g −1 at 50 mA g −1 and exhibit a low overpotential of 0.57 V under a cutoff capacity of 1000 mA h g −1, outperforming most of the current metal‐oxide‐based cathodes. Abstract : An open‐structured Co9 S8 matrix with a sisal morphology is constructed and employed as oxygen cathode for Li–O2 batteries. Benefiting from its excellent interface between substrate and product, superior bifunctional catalytic activities, large accommodation for Li2 O2, and easy diffusion for O2, the Co9 S8 cathode exhibits excellent electrochemical performance, which is a very promising cathode for Li–O2 batteries.